CORO1A: a pan-cancer prognosis, diagnostic and immune biomarker based on breast cancer validation - Elihamu, Dilraba; Li, Yongxiang; Wang, Yiyang; Cui, Haiyan; Xing, Yiting; Peng, Haohao; Ismtula, Dilimulati; Guo, Chenming (Frontiers in Oncology, 2025)
IntroductionCORO1A, a constituent of the Coronins family, is a conserved protein throughout evolution that interacts with actin within the cellular environment besides being involved in various malignancy development.MethodsA comprehensive analysis examining the discrepancies in expression levels, survival outcomes, immune cell infiltration (ICI), and enrichment profiles was performed. The expression of CORO1A in breast cancer tissues was verified by immunohistochemistry, WB and RT-qPCR experiments. The effects of different expression levels of CORO1A on the growth and metastasis of breast cancer cell lines were verified by CCK-8, colony formation, Trasnwell and cell scratch experiments.ResultsThe findings revealed a heightened expression of CORO1A in the 66.7% of tumor types (22/33), CORO1A consistently demonstrates high diagnostic potential and variable prognostic significance across cancers. In particular, its diagnostic value in SKCM reaches as high as 98%, with a prognostic hazard ratio of 0.77. CORO1A often characterized by hypomethylation of its promoter region, which correlates with the ICI level. Enrichment analysis highlights the critical contribution of CORO1A in B cell receptor pathways and other immune-linked processes, CORO1A may have multiple potential roles in B-cell receptor pathways, involving aspects such as signal transduction regulation, cytoskeletal remodeling and migration, as well as interactions with other immune molecules. exerting a substantial influence on patient prognosis. CORO1A is highly expressed in breast cancer tissues. Breast cancer patients with high expression of CORO1A have a good prognosis. CORO1A knockdown inhibits the growth and metastasis of breast cancer cells, while overexpression is the opposite. Therefore, due to its high diagnostic sensitivity and prognostic value demonstrated in various cancers, CORO1A holds promise as a candidate molecule for novel targeted therapies.DiscussionCORO1A, as a promising research target, has demonstrated significant and specific capabilities in predicting disease prognosis, analyzing immune responses, and exploring therapeutic approaches for different types of tumors, further highlighting the necessity for in-depth research on it.